Computation-guided improved one-pot synthesis of macrocyclic cation-binding aromatic pyridone pentamers. Issue 42 (21st September 2016) - Zeng, Vicky Ziman; Su, Haibin; Li, Tianhu
Abstract : The use of polar DMF to relax the H-bonding-rigidified backbone leads to significantly improved yields forBOP -mediated one-pot synthesis of pentameric macrocycles. Abstract : By using polar DMF to relax the H-bonded rigid backbone and to lower the energetic penalty associated with the sterically-crowded environment, the yields forBOP -mediated one-pot synthesis of pentameric macrocycles can be improved from 10–25% as obtained in CH2 Cl2 to 13–47% when 15% DMF in CH2 Cl2 was used as the reaction medium.